Cops at War: How World War II Transformed U.S. Policing. Issue 2 (July 2021) - Schrader, Stuart
Abstract : World War II transformed policing in the United States. Many police enlisted in the military during the war, and in turn many veterans joined police forces following the victories of 1945. As wartime labor shortages depleted their ranks, police chiefs turned to new initiatives to strengthen and professionalize their forces, redoubling those efforts as growing fears of crime and internal security threats outlasted the global conflict. This article investigates the rapid growth of the military police, how African Americans responded to changes in policing due to the war, and these wartime experiences' lingering impacts. Based on research in obscure and difficult-to-find police professional literature, and closely examining New York City, it argues that the war's effects on policing did not amount to "militarization" as currently understood, but did inspire more standardized and nationally coordinated approaches to recruitment as well as military-style approaches to discipline, training, and tactical operations.